Model Konseling Keterampilan Hidup Dalam Meningkatkan Kemampuan Hubungan Sosial Santri (Studi di Pondok Pesantren Babussalam Kabupaten Kapuas ) - Solikin, Asep (Anterior Jurnal, 2013)
One of the cultural bases of pesantren is a form of pesantren education that is characterized by traditionalism. Islamic boarding schools as one of the educational institutions where students learn social skills should continuously improve the way to help students develop positive social skills, both within the pesantren and in the community. In implementation, social skills do not sufficiently ensure the success of the pesantren; interventions are not limited to teaching and training for students; but pesantren should develop an environmental culture that facilitates by instilling an increase in social skills into a comprehensive and disciplined pesantren management system, emphasizing relationship-bulding between students; religious teachers and pesantren leaders (Kiyai) and between pesantren and families, as well as pesantren provide effective behavioral management and academic instruction. The concept and stages of counseling life skills within a santussalam Babussalam district of Kapuas Regency are new things that exist in the world of messaging, including components to develop relationships, identify and clarify problems, assess and redefine problems in the form of skills, formulate goals and plan interventions, intervene to develop self-helping skills, and end and consolidate self-help skills. The manifestation of the students' social relations abilities at the Babussalam Islamic boarding school can be seen in the Ability to Empower and Build Skills.